Economic value of recreational resources: testing benefit transfer approaches - Shrestha, Ram Krishna, author; Loomis, John B., advisor; Sampath, Rajan K., committee member; Manfredo, Michael J., committee member; Seidl, Andrew F., committee member (Colorado State University. Libraries, 2000)
There have been various efforts recently to transfer the economic values of recreational resources from one site to another in the United States. In the case of typical non-market goods, the benefit transfer approach has been as useful as the standard nonmarket valuation techniques, such as, contingent valuation method (CVM) and travel cost methods (TCM), in recreation decision making. The most attractive feature of benefit transfer, instead of conducting primary research on non-market valuation, is the use of existing findings and attributes of the primary research. Obviously, benefit transfer could save significant amount of time and resources, if it is practiced in real world policy decisions. However, for the benefit transfer approach to be more useful, it has to demonstrate its scientific basis, theoretical consistency and methodological validity. The main objective of this study is to demonstrate the application of meta-analysis in taking the stock of information, knowledge, and methodological developments in economic valuation of recreational resources and use those results to real world benefit transfer. To this end, the existing CVM and TCM studies of the United States and Canada on outdoor recreation were gathered, and the meta-analyses were performed on the variables obtained from those studies. Since no so called panel effect was found in the datasets, classical liner regression models were estimated. The application of meta-regression models in benefit transfer were further tested and analyzed in terms of out of sample convergent validity confirmation. In this testing procedure the new studies from the United States, not included in the meta-regression models estimated previously, were used. Similar testing and analyses were also performed using international out of sample studies in order to evaluate the application of meta-analysis in international benefit transfer process. The paired t-test revealed that there was no convergence between the means of meta-regression models predicted WTP values and the original out of sample studies WTP values within the United States. However, significant convergence between those values in the international context was revealed. Interestingly, there were significant positive correlations between those values in both national and international cases.
Keywords: recreation; environmental science; studies; natural resources; decision making; air pollution; meta-analysis